2010
DOI: 10.1182/blood-2009-11-254755
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of a fully active, long-acting PEGylated factor VIII for hemophilia A treatment

Abstract: A long-acting factor VIII (FVIII) as a replacement therapy for hemophilia A would significantly improve treatment options for patients with hemophilia A. To develop a FVIII with an extended circulating half-life, but without a reduction in activity, we have engineered 23 FVIII variants with introduced surface-exposed cysteines to which a polyethylene glycol (PEG) polymer was specifically conjugated. Screening of variant expression level, PEGylation yield, and functional assay identified several conjugates reta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
223
0
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(240 citation statements)
references
References 42 publications
(49 reference statements)
10
223
0
7
Order By: Relevance
“…The t 1/2 of recombinant FVIII or recombinant human B-domain deleted FVIII infused into mice is significantly shorter in the absence than presence of VWF (18 minutes vs 5.9-7.6 hours, respectively). [24][25][26] We confirm this relationship and demonstrate that a minimal, N-terminal VWF fragment comprising D9D3 domains (S764-P1247) is sufficient to stabilize endogenous FVIII in Vwf 2/2 mice. Extending the circulatory lifetime of D9D3 by Fc fusion markedly prolongs endogenous FVIII survival in Vwf 2/2 mice but is insufficient to extend the FVIII t 1/2 in HA mice.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The t 1/2 of recombinant FVIII or recombinant human B-domain deleted FVIII infused into mice is significantly shorter in the absence than presence of VWF (18 minutes vs 5.9-7.6 hours, respectively). [24][25][26] We confirm this relationship and demonstrate that a minimal, N-terminal VWF fragment comprising D9D3 domains (S764-P1247) is sufficient to stabilize endogenous FVIII in Vwf 2/2 mice. Extending the circulatory lifetime of D9D3 by Fc fusion markedly prolongs endogenous FVIII survival in Vwf 2/2 mice but is insufficient to extend the FVIII t 1/2 in HA mice.…”
Section: Discussionsupporting
confidence: 67%
“…21,22 Several approaches have attempted to engineer FVIII with an extended plasma half-life (t 1/2 ). [23][24][25][26] Recombinant human B-domain deleted FVIII infused into a C57BL/6 mouse has a similar t 1/2 (4.3 hours) to that of endogenous murine VWF (;4.5 hours). 25,27,28 Selective conjugation of polyethyleneglycol (PEG) 24,26 or fusion of FVIII to the Fc domain of immunoglobulin G (IgG) 25 increases FVIII plasma t 1/2 by ;1.5-to 2-fold in mice [24][25][26] and humans.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Subsequent studies in haemophilic mice demonstrated a significantly extended half-life with di-PEGylated FVIII molecules and excellent in vivo efficacy compared with traditional BDD-FVIII (Fig. 2) [14]. A study in humans is currently ongoing.…”
Section: Chemical Conjugation To Prolong Protein Half-lifementioning
confidence: 97%
“…Mei et al (2006) showed that rFVIII expression in this cell line is 8 to 30-fold higher than the one obtained in other cell lines, such as HEK293 and BHK21 cells. 58 Bayer HealthCare is using this cell line for the production of Bay 94-9027 (damoctacog alfa pegol), a PEGylated recombinant factor VIII, 40,58 which is currently in a phase III clinical trial (clinicaltrials.gov).…”
Section: Recombinant Factor VIII Productsmentioning
confidence: 99%